IMPROVING STUDENT PRONUNCIATION SKILLS THROUGH PHONETIC SYMBOLS - Hermansyah, Sam; Kaur, Parwinder; Monteza, Ana Mae M.; Dennison.J, Evans; Mohamed S.H, Sheik (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2025)
This study aimed to explore the effectiveness of phonetic symbols in enhancing the pronunciation skills of second-semester students in the English Department at the University of Muhammadiyah Sidenreng Rappang. The research utilized a quasi-experimental design involving two groups: an experimental group that was taught using phonetic symbols and a control group that followed conventional pronunciation methods. Both groups underwent pre-tests and post-tests to evaluate their pronunciation abilities. Results were analyzed using t-tests with the aid of SPSS software. The findings revealed a significant improvement in the pronunciation skills of the experimental group, with the post-test scores showing a substantial increase compared to the control group. Additionally, the students expressed a strong interest in using phonetic symbols for pronunciation practice, as indicated by their responses to a questionnaire. This study concludes that teaching pronunciation through phonetic symbols effectively enhances students' pronunciation abilities and is well-received by learners.